2007
DOI: 10.2174/157018007780077363
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Muscarinic Receptors in the Control of Acute Opioid Withdrawal

Abstract: This study was undertaken to determine which muscarinic receptors mediate parasympathetic responses in the ovine submandibular gland. The effects of selective muscarinic blocking agents on secretory and vascular responses to electrical stimulation of the chorda-lingual nerve were determined and morphological correlates were assessed by Western blotting. Anaesthesia was induced and maintained with sodium pentobarbitone (Sagatal; 15-30 mg kg _1 I.V., then 0.1_0.3 mg min _1 kg _1 I.V.). The ipsilateral ascending … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2009
2009

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…Furthermore, a large proportion of the contraction due to opioid withdrawal is caused by Ach release since it can be blocked by atropine or hyoscine [ 19 - 22 ]. Also, it has been demonstrated that also selective muscarinic receptors antagonists are able to influence opioid withdrawal in vitro [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a large proportion of the contraction due to opioid withdrawal is caused by Ach release since it can be blocked by atropine or hyoscine [ 19 - 22 ]. Also, it has been demonstrated that also selective muscarinic receptors antagonists are able to influence opioid withdrawal in vitro [ 45 ].…”
Section: Discussionmentioning
confidence: 99%